Midlife in the United States (MIDUS): Psychological Experiences Follow-Up Study, 1998 - Wethington, Elaine ([Verlag nicht ermittelbar], 2005)
The Midlife in the United States (MIDUS) data collection was a collaborative, interdisciplinary investigation of patterns, predictors, and consequences of midlife development in the areas of physical health, psychological well-being, and social responsibility. This component of the first MIDUS data collection was designed to understand popular metaphors of personal turmoil and change, such as the "midlife crisis," the "change of life," the "empty nest syndrome," and more. The primary objective of the Psychological Experiences Study was to explore how adults perceive psychological change in their lives. The study used questions derived from John Clausen's definition of "turning points" and other sources to collect data on self-perceived psychological changes involving work, important relationships, views about the self and dreams, beliefs about the midlife crisis, and recent major life events and transitions. This study was a random telephone follow-up of 724 respondents of the original MIDUS random-digit-dial sample. Part 1 of this collection consists of the quantitative data obtained from the telephone interviews. Part 2 includes the open-ended responses to selected questions from the telephone interviews.